Highly Radiation Sensitive Type IA FBGs for Future Dosimetry Applications - Zhang, Lin; Faustov, A. V.; Saffari, Pouneh; Gusarov, Andreï I.; Wuilpart, Marc; Megret, Patrice; Kalli, Kyriacos; Koutsides, Charalambos (My University, 2012)
We have studied Co 60 gamma-irradiation effect on the characteristics of Type IA fiber Bragg gratings. A record Bragg peak shift of 190 pm was observed for a grating written in Fibercore PS-1250/1500 photosensitive fiber at a radiation dose of 116 kGy. Type IA and Type I gratings show different kinetics under radiation and during post-radiation annealing, which can be used for the design of a grating based dosimetry system.
Keywords: Bragg peaks; Gamma irradiation; Photosensitive fibers; Dosimetry; Fiber bragg gratings; Ionizing radiation; Fibers